Nanoporous Copper Films: How to Grow Porous Films by Magnetron Sputter Deposition - Michał A. Borysiewicz; Patrycja Barańczyk; Jakub Zawadzki; Marek Wzorek; Rafał Zybała; Beata Synkiewicz-Musialska; Paweł Krzyściak (Crystals, 2024)
Porous copper films used in current collectors have been shown to improve the stability of Li-ion batteries. They can be applied in Si-based photodiodes, sensors or as microradiators. Their fabrication, however, remains a challenge. In this work, we report on the direct deposition of porous copper films using magnetron sputtering in regular chamber geometry. We show how by using appropriate process gases and substrate temperatures, it is possible to control the morphology of the deposited films. In particular, the optimization of the argon to oxygen flow ratios and flow values leads to small porosification of the deposited copper films. Further, heating the substrate during deposition enables the growth of pore sizes into mesoporous and macroporous ranges. This approach is scalable, and since it does not require glancing angle deposition enables the easy coverage of large surfaces with uniformly porous films.